UBuntu and the law : African ideals and postapartheid jurisprudence - Cornell, Drucilla; Muvangua, Nyoko (Just ideas., 2012)
This is the first comprehensive casebook to address the relationship of ubuntu to law. It also provides the most important critical articles on the use of ubuntu, both by the Constitutional Court and by other levels of the judiciary in South Africa.